Humanity and the 21st century’s resource gauntlet: a commentary on Ripple et al.’s article “World Scientists’ Warning to Humanity: a Second Notice” - Kayal,Mohsen; Lewis,Hannah; Ballard,Jane; Kayal,Ehsan (PeerJ Preprints, 2018)
The 21st century will undeniably represent a major turn in the development of human societies, as Earth’s limiting resources can no longer support the current pace of material consumption (supplemental file S1). In this context, Ripple et al. (2017) identified thirteen critical shifts in our ways of life to reduce humanity’s ecological footprint and achieve sustainable development. While we endorse the pertinence and urgency of this call, we direct attention to critical shortcomings in the proposed solutions, which limit their potential to promote sustainability. Indeed, several prescriptions in Ripple et al. address symptoms rather than root causes, or seem to result from a simplistic consideration of inherently complex processes. We emphasize the importance of accounting for historical patterns and underlying drivers of the global socio-economic system, especially in relation to wealth inequality, human demography, and food production, which need deeper consideration than presently given in the warning and subsequent follow-up articles. Without such considerations, this second warning to humanity can be interpreted as prescriptive suggestions from a narrow, western-biased vision of the global socio-ecosystem, rendering it all but ineffective.
Keywords: Sustainability; Inequalities; Demography; Food production; Resource flow; Waste; Ecological foodprint; Western bias; Sustainable solutions